Development of navigation aid for visually impaired person - Hossain, Eklas (Kulliyyah of Engineering, International Islamic University Malaysia, 2010)
Researches on walking support system for Blind have been facing challenges in detecting information about terrain, especially of stairs and holes in front of the user. In detecting terrain, researchers have tried different sensors like ultrasonic, laser, camera etc., and different algorithm; however, satisfactory outcome has not yet been achieved and white cane is still the most used walking support for the blind people. This is because almost all the research outcomes failed to address the crucial requirements of the walking support systems, like low energy requirement, light weight, hole and stair detection capabilities. In this research a belt equipped with four ultrasonic sensors and one infrared sensor, wearable around the waist is developed for smooth navigation of a visually impaired person. In the design of the new device all of the above issues have been considered and implemented successfully. A mathematical model has been developed based on the specifications of the ultrasonic sensors to identify optimum orientation of the sensors for detecting stairs and holes. These sensors are connected to a microcontroller along with a laptop so that sufficient data is available for analyzing terrain on the walkway of the blind. Based on the analyses of the acquired data an algorithm capable of classifying various types of obstacles is developed. Later the computer is removed and a microcontroller is used for the system, which is the device, named 'Belt for Blinds' to help them navigate through detection of their environment. The device is also equipped with a servo motor and a buzzer to generate outputs that inform the user about the type of the obstacle ahead. Besides, image processing was also done to analyze images of obstacles like stair up, and stair down, but it did not show worth result.